Biyofilik Tasarım İlkelerinin İç Mimarlıkta Psikolojik Göstergeler Üzerindeki Etkileri: Literatür İncelemesi - Şahin, Cemile Yüsra (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
The psychological effects of interior spaces on users have become increasingly important in the fields of interior architecture and environmental psychology. The decline in human interaction with nature may negatively affect individuals’ psychological well-being. In this context, biophilic design aims to strengthen the innate connection between humans and nature through the built environment. This study examines the effects of biophilic design principles on users’ psychological indicators using a literature review methodology. Within the scope of the research, studies published between 1992 and 2025 in the Scopus, Web of Science, and Google Scholar databases were reviewed, with a particular focus on indicators such as stress, attention restoration, psychological well-being, and spatial satisfaction. The findings indicate that biophilic design elements, including natural daylight, vegetation, water features, and natural materials, positively influence users’ psychological states by reducing stress and enhancing spatial satisfaction. However, the reviewed studies were found to be predominantly based on short-term investigations with limited sample sizes. Consequently, biophilic design is considered an important approach for enhancing user experience in interior spaces, while future research should focus on more comprehensive and long-term investigations.